2018
DOI: 10.25134/erjee.v6i2.1238
|View full text |Cite
|
Sign up to set email alerts
|

Using Blogs in Teaching Tertiary Esl Writing

Abstract: Anchored on the Technological, Pedagogical and Content Knowledge or TPACK Framework (Koehler & Mishra, 2009) and Substitution, Augmentation, Modification and Redefinition or SAMR Model of Technology Integration into the classroom (Puentedura, 2014), this study investigated a corpus of 58 blog posts written by ESL learners through weblogs. It aimed to determine the views of students on the use of blogs in learning English writing skills and to explore students' feedback on the advantages of blogging as a virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 13 publications
4
27
0
Order By: Relevance
“…The experience of travelling and writing about the local attractions of one's city via a personalized blog was reported to increase writing motivation, boost autonomous, reflective and collaborative learning, raise cultural awareness and have positive impacts upon learners' self-expression and L2 writing improvement. These findings are in line with those of several studies regarding the advantages of blog use in ELT (Akdag and Ozkan, 2017;Aydan, 2014;Aydin, 2014;Campbell, 2003;Featro and DiGregorio, 2016;Grami, 2012;Gunduz, 2016;Kovalchuk and Krasnokutska, 2017;Kuimova and Zmekov, 2016;Johnson, 2004;Lee, 2010;Mabuan, 2018;Musa, 2016;Nepomuceno, 2011;Pinkman, 2005;Sun and Chang, 2012;Zhang, 2010). The findings of the study about the affordances of travel blog writing also support the suggestions of Pascual (2019), Pascual Oliva (2017) and Romaniukha et al (2020) in that integration of this genre into EFL settings would develop linguistic skills, enhance verbal creativity and increase learning motivation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The experience of travelling and writing about the local attractions of one's city via a personalized blog was reported to increase writing motivation, boost autonomous, reflective and collaborative learning, raise cultural awareness and have positive impacts upon learners' self-expression and L2 writing improvement. These findings are in line with those of several studies regarding the advantages of blog use in ELT (Akdag and Ozkan, 2017;Aydan, 2014;Aydin, 2014;Campbell, 2003;Featro and DiGregorio, 2016;Grami, 2012;Gunduz, 2016;Kovalchuk and Krasnokutska, 2017;Kuimova and Zmekov, 2016;Johnson, 2004;Lee, 2010;Mabuan, 2018;Musa, 2016;Nepomuceno, 2011;Pinkman, 2005;Sun and Chang, 2012;Zhang, 2010). The findings of the study about the affordances of travel blog writing also support the suggestions of Pascual (2019), Pascual Oliva (2017) and Romaniukha et al (2020) in that integration of this genre into EFL settings would develop linguistic skills, enhance verbal creativity and increase learning motivation.…”
Section: Discussionsupporting
confidence: 88%
“…Blogs are reported to develop linguistic skills, particularly writing and reading as well as grammar and vocabulary, enhance interaction and collaboration, build confidence in writing, encourage autonomous learning, augment analytical and critical thinking skills, increase writing and reading motivation, sense for responsibility and desire for lifelong learning (Akdag and Ozkan, 2017;Aydan, 2014;Aydin, 2014;Campbell, 2003;Featro and DiGregorio, 2016;Grami, 2012;Gunduz, 2016;Kovalchuk and Krasnokutska, 2017;Kuimova and Zmekov, 2016;Johnson, 2004;Lee, 2010;Mabuan, 2018;Musa, 2016;Nepomuceno, 2011;Pinkman, 2005;Sun and Chang, 2012;Zhang, 2010). On the other hand, blog use in English lessons is said to have some challenges like complicated tasks, intense workload, and technological limitations like internet problems or unavailability of computers (Aydan, 2014;Featro and DiGregorio, 2016;Kovalchuk and Krasnokutska, 2017;Mabuan, 2018). Among blog types, travel blogs can present certain benefits to language learners, yet this type of blogging has received little attention in ELT literature.…”
Section: Blogs In Writing Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second study used Facebook as their virtual classroom and found that Facebook helps to engage the students on the path of personal development (Milošević et al, 2015). Moreover, other study concluded that blog offered online peer engagement (Mabuan, 2018). Other study also found that students' English language productivity increased using digital platforms .…”
Section: Introductionmentioning
confidence: 98%
“…Adas & Bakir [10] noted that blended learning can be a solution to the writing problem since it allows the teaching and learning writing less monotonous. Furthermore, current practice in teaching writing trough distance learning is mostly used blog as a learning tool (such as in (Nepomuceno [11], Artvianti [12], Shana & Abulibdeh [13], Kuimova & Zvekov [14], and Mabuan [15]). However, the use of social media in teaching writing remain unexplored since most previous studies on the use of social media to teach writing focus on discovering the role of social media to assist learning and limited studies about the used of social as a medium to teach and learn English skill, particularly writing.…”
Section: Introductionmentioning
confidence: 99%